Penerapan Strategi Pemasaran Dalam Mempertahankan Bisnis Umkm Di Jombang Pada Masa Pandemi (Studi UMKM Toko Bunga Ibin Menganto) - Ahmad Habib Alaydrus; Agus Widarko; Mohammad Rizal (UNIVERSITAS ISLAM MALANG, 2022)
Abstract This study aims to determine the marketing strategy in maintaining business at the Ibin Menganto Flower Shop during the COVID-19 pandemic using a marketing mix strategy that can be applied to business actors. This study uses a qualitative method, namely a case study that produces descriptive data set out in words. Sources of data in this study using data collection techniques in this study the authors made a direct visit to the Ibin Menganto Flower Shop to conduct personal interviews with the owner, Mr. Sudarmono. Equipped with sales data for the past few years. The researcher concludes that there are several discussions, namely Strategy, Constraints and Solutions. The strategy applied to the Ibin Menganto Flower Shop is the Marketing Mix (Product, Promotion, Price, and Place). Product strategy in the form of innovation of bougainvillea cuttings, skull cuttings, and rose cuttings. The Price Strategy is that every purchase of a bouquet gets a bonus mask, and the Place Strategy a comfortable and cool atmosphere because it is naturally planted with many trees. Promotion strategies are in the form of price discounts, banners, social media, although they cannot be implemented optimally due to the lack of community digital levels. Then, the business solution at the Ibin Menganto Flower Shop in dealing with COVID-19 is to maintain cash flow, product innovation and maximize social media Keywords: Marketing Strategy, Marketing Mix, Covid-19 Pandemic.